2007
DOI: 10.1097/sla.0b013e318123fbdf
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted Laparoscopic Versus Open Right Colectomy

Abstract: HALC retained the same short-term benefits of the pure laparoscopic approach. The technique is associated with a slightly increased but acceptable operative time. Aside as a useful adjunct in complex laparoscopic procedures, the hand-assisted laparoscopic technique is also a useful, if not more effective, alternative for patients with right-sided colonic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 29 publications
9
89
1
7
Order By: Relevance
“…As mentioned earlier, laparoscopy and transverse laparotomy might have various advantages on short-and longterm outcome compared to a midline laparotomy. Patients might experience less postoperative pain, have possibly a better pulmonary function, less wound dehiscence, and significantly less incisional hernias [3,5,7,9,13]. Also two meta-analyses [4,8] have suggested a transverse approach is superior to the midline incision, because of its better anatomical and physiological principles and therefore less prone to develop short-or long-term abdominal wall complications.…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned earlier, laparoscopy and transverse laparotomy might have various advantages on short-and longterm outcome compared to a midline laparotomy. Patients might experience less postoperative pain, have possibly a better pulmonary function, less wound dehiscence, and significantly less incisional hernias [3,5,7,9,13]. Also two meta-analyses [4,8] have suggested a transverse approach is superior to the midline incision, because of its better anatomical and physiological principles and therefore less prone to develop short-or long-term abdominal wall complications.…”
Section: Discussionmentioning
confidence: 98%
“…However, pure LACS has several disadvantages, such as requiring at least 2 physicians who are familiar with the procedure and prolonging the operating time, as well as needing more staff and limiting the availability of operating theaters. Previously, it was reported that pure LACS achieves the same or better outcomes as conventional laparotomy (CL) with regard to wound infection, hospital stay, and survival, together with superior cosmetic results (7)(8)(9)(10). In Europe and the USA, hand-assisted laparoscopic surgery (HALS) (HH) is more widely used than pure LACS.…”
Section: Introductionmentioning
confidence: 99%
“…Large randomized trials have demonstrated oncologically equivalent outcomes for laparoscopic and open colon resection. [1][2][3] Laparoscopy has the additional benefits of improved postoperative recovery, reduced analgesia requirements and shorter length of hospital stay. 2,[4][5][6] There is also evolving evidence for long-term benefits, including reduced bowel obstructions and ventral hernias.…”
mentioning
confidence: 99%
“…[1][2][3] Laparoscopy has the additional benefits of improved postoperative recovery, reduced analgesia requirements and shorter length of hospital stay. 2,[4][5][6] There is also evolving evidence for long-term benefits, including reduced bowel obstructions and ventral hernias. 4,[7][8][9] There is wide variation among laparoscopic colon resection techniques, including the approach for mobilization (medial-to-lateral v. lateral-to-medial) and the extent of intracorporeal vessel ligation, bowel division or anastamosis.…”
mentioning
confidence: 99%